Penerimaan Aplikasi Loklok Menggunakan Metode Technology Acceptance Model (TAM) oleh Masyarakat Jakarta - Adzani, Adinda Mutiara; Aula, Raisah Fajri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Nowadays, the development of communication and information technology has brought major chages in various aspect of life, one of them is in entertainment aspects. For example video streaming technology. Video streaming technology has been part of modern society. Loklok is of video streaming technology application which is popular in Indonesia. The purpose of this research is to analyze the acceptance video streaming technology on Loklok application and find out whether it can be generally acceptance by the people of Jakarta. This research was done for loklok application users. Loklok is an application or platform that provides video streaming services with many varieties of genres such Korean dramas, western films and animations. The conceptual model of technology acceptance assessment is based on the Technology Acceptance Model (TAM), which is a research model that analyzes the factors that influence the acceptance of computer technology. The statistical analysis used is the partial least squares structural equation model. This research uses quantitative methods with data collection techniques in the form of filling out online questionnaires through Google Forms with the number of respondents determined by the Slovin formula and sampling techniques using simple random sampling. This study uses PLS-SEM data analys with SmartPLS tools with a sample size of 100. The results of this study indicate that the variables Perceived Usefulness -> Attitude of use, Perceived ease of use -> Attitude of use, Attitude of use - > Behavioral Intention Of Use and Behavioral Intention Of Use -> Actually System Use are positive which means that the LokLok application is well received by the Jakarta Community.